If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q(p + -1q) = 0 (p * q + -1q * q) = 0 (pq + -1q2) = 0 Solving pq + -1q2 = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add 'q2' to each side of the equation. pq + -1q2 + q2 = 0 + q2 Combine like terms: -1q2 + q2 = 0 pq + 0 = 0 + q2 pq = 0 + q2 Remove the zero: pq = q2 Divide each side by 'q'. p = q Simplifying p = q
| a-20=50 | | 2(3n-5)=(3n+3)+1 | | 5p+7-5=-7(p-3) | | -2(t-4)+5t=9t-7 | | 0.08(y-4)+0.12y=0.10y-0.01(30) | | 11x=133 | | 10z-55=75 | | 7(5x+1)=2x+3 | | x/25=10/15 | | x/25=10/25 | | X^2x-3=0 | | 2(x+3)-7x=18-5(x+14) | | X^2+20x-24=0 | | x^2-71=0 | | 13z=12/8 | | 18/4=27/n | | 7y=5/9 | | 9y=12/6 | | 0.30x+0.30(50)=0.15(40) | | x-(5-3x)=(3m-8) | | -5x+30-9=21 | | 0=4x^2-36x+72 | | -8x+12=2x | | 0.04x^2-0.5x+0.08=0 | | ((160(y^5)(z^3))/(-20(y^9)(z^-6))) | | 3/8x-1/4=1/5 | | 10/4a-6=-1 | | 7/4a-3=-1 | | -7z-7z=-z-3-8z | | a/7=(a-2/5) | | -5x+8x^2-10x+5= | | 8w+6w=56 |